OPTIMIZATION OF TARGET CALCULATION METHOD FOR LEATHER SKIVING AND STAMPING: CASE OF LEATHER FOOTWEAR INDUSTRY - Muhammad Saleem Arain; Muhammad Ali Khan; Muhammad Ahmed Kalwar (International Engineering Journal For Research & Development, 2020)
Time and motion study are subject of major concern for footwear especially on the production floor. It plays a remarkable role in calculation of target for various operations of leather upper cutting and stitching. Since, targets are associated with the cost so the non-value added time in the targets cannot be affordable. A little ignorance in targets can case the greater loss of resources (time and money). In the case footwear company, there has been the fight of workers and Industrial Engineering department since so long on the targets because of direct involvement of worker in the time study. Involvement of worker in the calculation of target cause decrease in targets because worker`s single micro motion (of few seconds) at the moment of time study can cause the loss of thousands to the company. In this regard, the method of calculation of target of leather skiving and stamping was formulated. Some pieces of leather were got issued from the leather store of the case company and cut into pieces for operations (stamping and skiving) to be performed on them. Both operations were split into the series of micro motions and 10 observations for each micro motions were collected from five workers individually (2 observations from each worker). The average time of micro motions was considered as standards and for the calculation of overall time of the operations was calculated by help of developed formulae. Data was entered and formulae were applied in the excel spreadsheet and charts were also plotted. For plotting the 3 dimensional chart, statistical package for social sciences was used. An excel spreadsheet was developed (containing the all formulae) for the purpose of target calculation for both operations. It was concluded that calculated targets as per suggested method for stamping and skiving were 4.4% and 4.74% greater respectively in the comparison of calculated targets as per old method.